A 16-Year Review of Participant Diversity in Intervention Research Across a Selection of 12 Special Education Journals. (April 2018) - Sinclair, James; Hansen, Sarah G.; Machalicek, Wendy; Knowles, Christen; Hirano, Kara A.; Dolata, Jill K.; Blakely, Allison W.; Seeley, John; Murray, Christopher
Given the continued changes in demographic diversity of students in the United States, it is important to ensure that participants included in special education research reflect the diversity of the classroom. We examined 16 years of intervention research across 12 special education journals to evaluate the extent to which diverse student populations (e.g., race, ethnicity, disability, sexual orientation, English language learner status) were included in published intervention research. We analyzed 495 intervention articles (9.6%) out of 5, 180 total articles. Results revealed that progress has been made in the inclusion of diverse participants in special education intervention research compared with previously conducted reviews, yet some racial and ethnic populations are still underrepresented. We discuss strategies for recruitment and retention of underrepresented diverse populations.